LINKING JOB SECURITY TO PSYCHOLOGICAL WELL-BEING THROUGH JOB SATISFACTION POLICE - Netty Merdiaty (International Journal Labs, 2024)
This study aims to investigate the direct effect of job security on psychological well-being with job satisfaction as a mediator among the Police in Indonesia. The research method used a quantitative approach with 101 police respondents. The analysis results showed that all variables met the criteria of validity and reliability. There is no problem of multicollinearity between latent variables. The study highlights the importance of job security, job satisfaction, and psychological well-being among police officers and employees in the public organization. The analysis showed that job security significantly influenced job satisfaction and psychological well-being. Although job satisfaction may not play the role of maximal mediation, the importance of a supportive work environment in improving job satisfaction and psychological well-being among police officers is also highlighted. The rigorous methodology and comprehensive analysis provide valuable insights into the relationship between job security, job satisfaction, and psychological well-being in Indonesia's law enforcement context